Engineering chondrogenesis with mesenchymal stem cells in gene-transferred co-culture systems - Tan, Neptina Shuyi. (2009)
The possibility of engineering articular cartilage using a novel co-culture system is being investigated in this study. In this 42 days co-culture study, autologous rabbit chondrocytes were transfected with Adenovirus containing the transforming growth factor-β3 (TGF- β3) gene and co-cultured with synovium-derived mesenchymal stem cells (SMSCs) in alginate hydrogels. It is hypothesized that the chondrocytes would produce TGF- β3 to induce chondrogenesis in the SMSCs. Real-time quantitative polymerase chain reaction (PCR), Enzyme-Linked ImmunoSorbent Assay (ELISA), flow cytometry and immunochemical staining were employed to determine successful chondrogenesis, levels of TGF- β3 expression, viability of the chondrocytes and validate presence of characteristic proteins present in cartilage respectively. Real-quantitative PCR results have shown significant expression of Collagen II in SMSCs, indicating successful chondrogenesis. However, the immunochemical staining could not confirm these results. TGF- β3 expression levels were high, 10-100ng/ml, for the first week before decreasing to a stable level of 0.5ng/ml after Day 18. Another 42 days study was performed with only TGF- β3 transfected chondrocytes to analyze the relation between TGF- β3 expression and the viability of the transfected chondrocytes when cultured in alginate hydrogel. Results showed a direct relation between the percentage of transfected chondrocytes in the hydrogel and levels of TGF- β3 expression. Other side studies undertaken have also given several insights into improving the current co-culture system.